Federalism and the welfare state in a multicultural world - Johnston, Richard, 1948-; Kymlicka, Will; Myles, John; Goodyear-Grant, Elizabeth, 1976- (Queen's policy studies., 2018)
"Social policy is integral to mitigating divisions of class, region, language, race and ethnicity, and its underlying values of solidarity and risk-sharing also make it a critical mechanism for nation-building. Whether social policy actually accomplishes these goals is variable and contested, however. The mere fact of pooling risk poses the question of who "we" are, with exclusionary implications as much as inclusionary ones. Despite various challenges, until the 1990s there was some evidence that Canadian social policy played an integrative role, providing a counter-narrative to pessimistic claims that federalism and diversity undermine the integrative potential of social policy. Today, however, the Canadian model is under strain, reflecting changes in both the welfare state and the immigration-citizenship-multiculturalism regime. As the volume illustrates, there are clear trends that, if unchecked, may exacerbate rather than overcome important social cleavages. We are therefore at a crucial moment to re-evaluate the role of social policy in a federal state and multicultural society, the central task of this volume. If federalism and diversity challenge traditional models of the nation-building function of social policy, they also open up new pathways for social policy to overcome social divisions. Complacency about, or naive celebration of, the Canadian model is unwarranted, but it is premature to conclude that the model is irredeemably broken, or that all the developments are centrifugal rather than centripetal."--